Sol–Gel Synthesis and Crystal Nucleation of Photosensitive Au/Ag- Containing Glasses of Lithium Silicate System - A. Sycheva, Galina (Journal of Applied Solution Chemistry and Modeling, 2016)
A sol–gel method has been proposed for obtaining the sintering mixture used in the preparing of a photosensitive Au/Ag-containing glasses of the Li2O - SiO2 system. It has been established that the use of sol–gel method for the production of the batch for synthesizing photosensitive Au/Ag-containing glasses gives more homogeneous distribution of Au/Ag metals in the bulk of the glass. Crystal-nucleation main characteristics have been defined in a large area of compounds of photo-structured compositions of a lithium-silicate system (23.4–46.0 Li2O mol % by analysis) both for spontaneous and catalyzed nucleations. The spontaneous (homogeneous) nucleation happened in the samples without any photosensitive metals and with photosensitive gold–silver additives (0.05 wt % above 100%) without irradiation; the catalyzed (heterogeneous) nucleation happened in the samples with photosensitive silver ore gold additives under x-ray CuKa irradiation. The ranges of the compositions of the glasses in which the effect of catalyzing irradiation is reversed (suppressing nucleation in accordance with the autocatalytic mechanism) under certain conditions. The spontaneous and catalyzed nucleation of crystals in the glasses of Li2O–SiO2 system caused by the addition of photosensitive impurities and X-ray irradiation was analyzed in glasses with a very wide range of compositions in Li2O–SiO2 system. Composition ranges with positive (+) and negative (-) differences in the rates of catalyzed and spontaneous steady-state nucleation were established. This finding point is favorable for obtaining photostructured (photosensitive) materials. The concentration limit was determined to be 37.98 mol % Li2O. About this value, we observe a modification of the mechanism of nucleation of crystals. The behavior of crystal nucleation in photostructured glasses under X-ray irradiation changes to the reverse: autocatalytic nucleation is suppressed rather than induced by x-ray CuKa irradiation. These peculiarities of crystallization mechanism in glasses under study give one the possibility to choose the correct composition range depending on the problems facing researchers.